Effect Of Digital Finance And Digital Payment On Sme Performance Mediated By Risk Perception - Zayyani, Erika Zayyani; Suryani, Embun (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to analyze how SME performance is influenced by digital finance and digital payment, mediated by risk perception. This study employs a quantitative approach using primary data. Data were collected through interviews using a questionnaire as the research instrument. The population of this study includes SMEs in the creative economy sector that have adopted digital finance and digital payment. The research sample was selected based on research needs, with a total of 130 respondents. Data analysis was conducted using SmartPLS. The results indicate that digital finance has a significant positive effect on SME performance, and risk perception is not proven to mediate the relationship between digital finance and SME performance. Meanwhile, digital payment is found to have no effect on SME performance, whereas risk perception is proven to mediate the relationship between digital payment and SME performance. This research is expected to provide insights for SME actors regarding the use of digital finance and digital payment in business methods. For future researchers, it is recommended to expand the geographical scope of the study and explore other variables that influence digital technology adoption, such as government regulations or cultural factors.